Strategi pembelajaran pengalaman berasaskan model kolb dalam pendidikan perakaunan - Rohaila Yusof, -; Norasmah Othman, -; Faridah Karim, - (penerbit ukm, 2005)
Learning styles are neither individualistic and reflect the way individuals perceive and process information from educational environment. A quasiexperimental study involving 145 accounting students from a public university was carried out to test the effect of two learning strategies on the development of cognitive skills. In this study, cognitive skills are made up of two components namely, technical skills (low-level cognitive) and analytical skills (high-level cognitive). The experimental group was put through the KOLB Learning Cycle (KLC) strategy, and the control group went through the traditional learning strategy, which depended mainly on lectures. Before treatment, pretest data indicated no difference in the learning styles of the two groups. Posttest results (two-way ANOVA) showed no significant interaction effect was found between learning styles and treatment. Results on the relationship between the four phases of learning in the KLC and the development of cognitive skill indicated that the active experimentation phases had a high relationship with the achievement of cognitive skills. Activities in phase three (experimentation) and phase four (conceptual abstract) contributed towards the achievement of technical skills. Activities in phase 1 and phase 2 contributed towards the achievement of analytical skills.